Dampak Sosial Media Terhadap Perilaku Keagamaan Dan Moral Remaja Dalam Masyarakat Modern - Fadilah, Siti; Makbul, M. (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study examines the impact of social media on the religious and moral behavior of adolescents in modern society. Social media is an online socializing platform that allows people to interact and communicate with others without time and space constraints. However, on the other hand, social media can also be a platform for spreading negative information and hoaxes, and has the potential to lead teenagers to moral decline. So the purpose of this research is to understand the influence of social media on the religious and moral behavior of adolescents in the digital era. This research focuses on several aspects including the influence of social media on adolescents' religious values, the influence of social media on adolescents' morals and the role of parents and teachers in assisting adolescents in using social media. This research reveals the significant influence of social media on the religious and moral behavior of adolescents in modern society. The results show that social media opens space for teenagers to learn and practice religious values more easily, but also has the potential to plunge them into negative content that is contrary to religious values. Social media can also help teenagers build good character and morals, but on the other hand, it can encourage them to commit immoral acts. The role of parents and teachers is very important in assisting adolescents in using social media wisely and responsibly.